2016
DOI: 10.1590/1678-775720150511
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and morphometric analysis of three-rooted mandibular first molars in a Brazilian subpopulation

Abstract: The knowledge of the internal anatomy of three-rooted mandibular molars may help clinicians to diagnose and plan the root canal treatment in order to provide adequate therapy when this variation is present.Objectives:To determine the prevalence of three-rooted mandibular molars in a Brazilian population using cone beam computed tomography (CBCT) and to analyze the anatomy of mandibular first molars with three roots through micro-CT.Material and Methods:CBCT images of 116 patients were reviewed to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 25 publications
5
26
2
3
Order By: Relevance
“…Iranian population (3.1%) [15], but less than the frequency reported with the use of CBCT technique in Taiwanese population whose results were 33.3% [16] and 29% [17]. In contrast to this, our observation was higher than the frequency noted in Turkish -2.06% [18] and 2.58% [19] and in Brazilian population (2.6%) [20] using CBCT. As compared to our study, a higher values was noted by the previous studies carried out in Saudi Arabian population by conventional methods [10,11], this discrepancy may be seen due to change in sample size and the different methodology employed in these studies.…”
Section: Discussioncontrasting
confidence: 82%
“…Iranian population (3.1%) [15], but less than the frequency reported with the use of CBCT technique in Taiwanese population whose results were 33.3% [16] and 29% [17]. In contrast to this, our observation was higher than the frequency noted in Turkish -2.06% [18] and 2.58% [19] and in Brazilian population (2.6%) [20] using CBCT. As compared to our study, a higher values was noted by the previous studies carried out in Saudi Arabian population by conventional methods [10,11], this discrepancy may be seen due to change in sample size and the different methodology employed in these studies.…”
Section: Discussioncontrasting
confidence: 82%
“…Nonetheless, there was disagreement observed in prior CBCT studies 20,23-25 used for the identification of three-rooted PFM in the mandibular arch. However, two studies 20,23 showed the highest occurrence (33.3% and 29%) whereas another very low occurrence was noted in the other two studies was 2.6% 24 and 2.5%, 25 respectively. Furthermore, CBCT is considered an ideal diagnostic imaging modality in the field of modern dental practice including endodontics.…”
Section: Discussionmentioning
confidence: 80%
“…No primeiro caso clínico apresentado, foi observado a necessidade de se estender o acesso para a região disto-lingual para facilitar o encontro do radix entomolaris. Fato este que, vai de encontro com os achados literários que evidenciam uma maior probabilidade de esta raiz supranumerária está localizada nesta região (RODRIGUES et al, 2016). No terceiro caso a variação anatômica foi possível ser encontrada devido a uma correta análise radiográfica, enquanto que no segundo a elevada destruição coronária proporcionou o achado dessa raiz extra.…”
Section: Discussionunclassified